The lost manuscript - Rushmeyer, Mollie (Love Inspired, 2023)
Since the mysterious disappearance of her beloved Grandma June and separating from her husband, Alex, Ellora has felt adrift. Then comes an invitation from Alex to teach history at a summer program at Alnwick Castle in England. He's even found information about the location of a medieval manuscript that was her grandmother's obsession before she vanished.